Relações entre memória episódica, sintomas depressivos e pensamento negativo repetitivo (PNR) em idosos - Fraga, Valéria Figueiredo (Universidade do Vale do Rio dos Sinos, 2024)
Population aging is an essential theme to explore in current studies, considering the significant changes we are facing in the global population profile. Additionally, depressive disorders are common among the elderly population. The manifestation of depressive symptoms in the elderly is more heterogeneous and less stereotyped than in younger populations, which can make it more challenging to systematize for professionals treating these patients. Nowadays, there is a concern with understanding the transdiagnostic factors associated with depression, and recent investigations suggest that repetitive negative thinking (RNT) is among these transdiagnostic factors for depression. Therefore, the objective of this dissertation was to assess the relationship between depressive symptoms and elderly individuals' performance in episodic memory tests, as well as to evaluate the associations between subjective cognitive complaints, selfreported depressive symptoms, repetitive negative thinking, and effective performance in episodic memory tasks. To achieve the dissertation's objective, two studies were conducted. Both studies are cross-sectional and quantitative. Data collected through standardized instruments were analyzed using the statistical program SPSS version 25, with the sample consisting of elderly individuals from Rio Grande do Sul. As for each of the studies, in the first study we have the Addenbrooke's Cognitive Examination, the Geriatric Depression Scale, the Free and Cued Selective Test with Immediate Recall, the WAIS-III Scale Digit Test, the Psychological Battery for Attention Assessment and Verbal Fluency Test. The results revealed that depression has a negative, weak to moderate, correlation with free recall from memory, attention and verbal fluency. In the second study, the Perseverative Thinking Questionnaire, the Geriatric Depression Scale, the Free and Cued Selective Reminding Test with Immediate Recall and the Cognitive Function Instrument were used. The results show that Repetitive Negative Thinking has a direct effect on depression, in which turn is associated with an increased perception of cognitive decline. Suggest a possible mechanism by which Repetitive Negative Thinking negatively affect depressive symptoms and increase a perception of cognitive decline.
Keywords: Envelhecimento; Memória episódica; Depressão; Pensamento negativo repetitivo; Aging; Episodic memory; Depression; Repetitive negative thinking; ACCNPQ::Ciências Humanas::Psicologia